An Empirical Study of Error Characteristics in Accounting Populations. - Ham, Jane; Losell, Donna; Smiellauskas, Wally (The Accounting Review, 1985)
Abstract ABSTRACT: This paper reports the error characteristics of five accounting categories using a new data set consisting of errors discovered during the audits of 20 companies throughout five years. The shape and variability of error amount distributions are described as well as the magnitude, direction, and types of errors making up these distributions. Four error rates are defined and their distributions presented and analyzed. Finally, three environmental factors (accounting category, industry, and firm-specific characteristics) are investigated for their impact on errors and error rates. In addition, the effect of firm size on error rates is tested.